Nestin and CD34 expression in colorectal cancer predicts improved overall survival. (3rd June 2021) - Tampakis, Athanasios; Weixler, Benjamin; Rast, Silvan; Tampaki, Ekaterini-Christina; Cremonesi, Eleonora; Kancherla, Venkatesh; Tosti, Nadia; Kettelhack, Christoph; Ng, Charlotte K. Y.; Delko, Tarik; Soysal, Savas D.; von Holzen, Urs; et al.
Abstract: Background: Nestin, a class VI intermediate filament protein of the cytoskeleton, and CD34, a transmembrane phosphoglycoprotein, are markers of progenitor cells. This study aimed to evaluate their expression and clinical significance in colorectal cancer. Methods: A clinically annotated tissue microarray, including 599 patients with colorectal cancer, was analyzed by immunohistochemistry. Furthermore, nestin and CD34 correlations with HIF-1a and a panel of cytokines and chemokines were assessed using quantitative reverse transcription PCR and The Cancer Genome Atlas dataset. Results: Expression of nestin and CD34 was observed only in the tumor stroma. Patients displaying high expression of nestin and CD34 demonstrated higher rates of T1 and T2 tumors ( p  = .020), lower vascular invasion ( p  < .001) and improved 5-year overall survival (65%; 95% CI = 55–73 vs 45%; 95% CI = 37–53) after adjusting for clinicopathological characteristics (HR: 0.67; 95% CI = 0.46–0.96). A moderate to strong correlation ( r  = 0.37–0.78, p  < .03) of nestin and CD34 was demonstrated for the following markers; HIF-1α, CD4, CD8, FOXP3, IRF1, GATA3, CCL2, CCL3, CXCL12 and CCL21. Conclusions: Combined expression of nestin and CD34 expression is associated with better overall survival possibly by modulating a favorable immune response.